DEVELOPING ENGLISH SPEAKING MATERIALS ORIENTED TO BRAIN ACCOMMODATION - Rachman, Siti Muthi'ah (Universitas PGRI Sumatera Barat, 2020)
The aims of this research are designing the speaking learning materials for seventh grade students of junior high school based on left- and right-brain accommodation, and to find out the appropriateness of the materials developed. The type of this research was Research and Development adapting the model proposed by Dick and Carey. Brain Dominance Test was employed to find out students’ brain dominance. The researcher also used needs analysis to develop the materials. The result of this study was English speaking materials for students oriented on left- and right-brain dominance. In terms of target needs, the students were expected to accommodate their left- and right-brain to obtain their knowledge, ability, and skills to communicate using English. In conclusion, the development of the English speaking materials oriented to left- and right-brain accommodation lead the students’ ability in English speaking.